2023
DOI: 10.1002/cjoc.202200714
|View full text |Cite
|
Sign up to set email alerts
|

Phototheranostic Nanoagents for Imaging‐Guided Treatment of Oral Cancer

Abstract: Comprehensive Summary Phototherapy showed almost a lack of drug resistance and, depending on the therapeutic effects of non‐invasive light‐stimulating photosensors. The side effects of phototherapy were greatly reduced compared to their traditional equivalents. Phototheranostic nanoagents had new properties in drug delivery, biocompatibility, targeting and response, in which traditional phototheranostic drugs can not possess. Recently, a large number of relevant studies have demonstrated that photodynamic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…In particular, NIR‐controlled photothermal nanoplatforms can regulate enzyme activity in cancer cells, leading to enhanced anti‐tumor effects. [ 25‐26 ] Wang et al . [ 27 ] designed NIR light‐responsive nanozymes by modifying ultra‐small platinum nanoparticles (Pt NPs) into the interior of various enzymes, which achieved local thermal therapy through the excellent photothermal conversion effect of Pt NPs mediating, thereby enhancing the enzyme activity.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In particular, NIR‐controlled photothermal nanoplatforms can regulate enzyme activity in cancer cells, leading to enhanced anti‐tumor effects. [ 25‐26 ] Wang et al . [ 27 ] designed NIR light‐responsive nanozymes by modifying ultra‐small platinum nanoparticles (Pt NPs) into the interior of various enzymes, which achieved local thermal therapy through the excellent photothermal conversion effect of Pt NPs mediating, thereby enhancing the enzyme activity.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Based on the above considerations, an aggregation-induced emission luminogen (AIEgen) was synthesized and applied as a photothermal agent. It generates heat upon aggregation state after NIR laser exposure, enabling photothermal therapy (PTT) and serving as a trigger for a hydrogel-based drug release system. However, the therapeutic outcome of PTT alone is still inadequate to interfere with the tenacious cellular activity of CSCs. ,, Recent clinical research has shown that patients who received dopamine receptor (DR) antagonists showed a reduced incidence of cancer metastasis due to efficient inhibition of DR expression and CSC proliferation. , …”
Section: Introductionmentioning
confidence: 99%